Impact of COVID-19 on digestive system: prevalence, clinical characteristics, outcome, and relation to the severity of COVID-19 - Walaa M. Hashem; Heba Abdelaziz; Dina E. Sallam; Moamen Abdelfadil Ismail; Ahmed Elmetwally Ahmed (SpringerOpen, 2022)
Abstract Background Coronavirus disease 2019 (COVID-19) is commonly associated with respiratory symptoms. However, gastrointestinal (GI) symptoms are increasingly recognized in COVID-19 patients. The aim is to study the prevalence and features of gastrointestinal manifestations in severe acute respiratory coronavirus 2 (SARS-CoV-2) infected patients and evaluate the outcome among the studied population. Results We enrolled adult patients with laboratory-confirmed COVID-19 admitted to Ain Shams University designated hospitals, Cairo, Egypt, from March 2021 to June 2021. The patients were assigned to a GI group and a non-GI group based on the presence or absence of one or more digestive symptoms. A total of 300 hospitalized COVID-19 patients were included, of which 104 (34.7%) had one or more digestive symptoms. They were compared with 196 COVID-19 patients without GI symptoms. The most common reported GI symptom was diarrhea (82.7%). GI symptoms' presence was higher in moderate cases. Patients with digestive symptoms presented for care later than those without (7.9±3.8 vs 7.4±7.2 days, P=0.5). Moreover, they have lower mortality, though non-significant (7.7 vs 12.8%, P=0.18). Patients with digestive symptoms had lower total leucocytic count (TLC), neutrophil count, neutrophil to lymphocyte ratio (NLR), platelet count, and higher serum sodium than those without digestive symptoms. Conclusion GI symptoms are prevalent among COVID-19 patients, and the most common was diarrhea. The presence of GI manifestations was not associated with increased mortality.